Guava botany, production and uses - Mitra, S. K. (Horticulturist) (Botany, production and uses., 2021)
"Guava is considered a minor tropical fruit (together with lychee, longan, durian etc.), although is the largest in terms of output. This is the first comprehensive book authored by an international team of experts, and covers botany, biotechnology, propagation, production, pests and diseases, postharvest, and processing"--